PENGARUH CITRA MEREK DAN DESAIN PRODUK TERHADAP LOYALITAS PELANGGAN PADA PRODUK CELCIUS KOTA SORONG - Sofia, Susetyowati; Mufti, Digor; Syahabuddin, Syahabuddin (LP2M Universitas Bina Bangsa, 2024)
This study aims to find out that Brand Image and Product Design have a positive and significant influence on Customer Loyalty of Celsius Products in Sorong City. This research includes descriptive research and surveys with quantitative data types. The data used in this study were customers / consumers of Celsius Sorong, which amounted to 80 people. Hypothesis testing was carried out using multiple linear regression analysis, with the independent variable being Brand Image as X1, Product Design as X2, and the bound variable being Customer Loyalty as the variable Y. The results of the hypothesis test for the partial test of the study showed that Brand Image did not have a positive influence but had a significant influence on Customer Loyalty, and Product Design had a positive and significant influence on Customer Loyalty Celsius products in Sorong City. Meanwhile, the results of the hypothesis test for the simultaneous test show that Brand Image and Product Design are also quite closely related to Customer Loyalty in Sorong City